The Impact of Posterior Corneal Astigmatism on Surgically Induced Astigmatism in Cataract Surgery - Liu W; Yang L; Liu J (International Journal of General Medicine, 2022)
Wenjie Liu,* Lichun Yang,* Jiewei Liu Cataract Department, Shanxi Eye Hospital, Taiyuan, Shanxi Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jiewei Liu, Email jieweiliu1967@163.comPurpose: This study aimed to evaluate the changes in posterior corneal astigmatism after cataract surgery and provide a theoretical basis to accurately evaluate the total corneal astigmatism (TA) to be corrected before toric intraocular lens (IOL) implantation.Patients and Methods: Sixty-two patients (89 eyes) who underwent phacoemulsification combined with toric IOL implantation (AcrySof IQ Toric SN6AT2-T9) at Shanxi Eye Hospital between January 2017 and September 2018 were enrolled. Surgically induced astigmatism of the posterior cornea (SIAPA) was analysed using vector analysis during pentacam examination.Results: The vector variances of keratometric astigmatism (KA), TA, and posterior corneal astigmatism (PA) preoperatively and postoperatively in the “with-the-rule (WTR) astigmatism” group and “overall patient” group were statistically significant (P < 0.05). A statistically significant difference was observed between surgically induced KA (SIAKA) and surgically induced astigmatism of the total cornea (SIATA) for all patients, including those with WTR astigmatism. For all patients, SIAKA was less than SIATA by 0.05 ± 0.21 D, and for patients with WTR astigmatism, SIAKA was less than SIATA by 0.09 ± 0.22 D. For patients in the “against-the-rule (ATR) astigmatism” group, there were no statistically significant differences between SIAKA and SIATA, although SIAKA was greater than SIATA by 0.03 ± 0.18 D. When PA ≤ 0.4 D or KA ≤ 2.0 D, SIAPA can be ignored. However, when PA > 0.4 D or KA > 2.0 D, ignoring SIAPA caused by cataract surgery incision will cause SIAKA in patients with WTR astigmatism to underestimate SIATA, while SIAKA in patients with ATR astigmatism will cause an overestimation of SIATA.Conclusion: SIA on the posterior corneal astigmatism may have a significant role on more precise planning of toric IOL implantation, especially in cases with higher preoperative anterior or posterior corneal astigmatism.Keywords: surgically induced astigmatism, SIA, posterior corneal astigmatism, PA, keratometric astigmatism, KA, total corneal astigmatism, TA